Testing Of Paenibacilus Polymyxa B32/77 Antagonism Bacteria Against Oil Palm Bottom Rot (Ganoderma Boninense) - Manalu, Anggiat; Susanti, Yuliana; Bahar, Edward (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The main problem faced by oil palm plantations is low productivity, including attacks by stem rot disease caused by the Ganoderma boninense fungus. The aim of the research was to determine the ability of bacteria (Paenibacilus polymyxa B32/77) to inhibit stem rot (G. boninense). Research methods are divided into two, namely in the field and in the laboratory. In the field, sampling of oil palm plants infected with stem rot disease. In the laboratory isolation, characterization and identification of the pathogen are carried out. Next, rejuvenating the bacterial isolate P. Polymyxa B32/77 and testing the inhibitory power of P. Polymyxa B32/77 against G. boninense using the cross streak method. The indigenous antagonistic bacteria (P. Polymyxa B32/77) came from isolated eucalyptus plants. Results of the bacterial antagonist test P. Polymyxa B32/77. unable to inhibit the growth of G. boninense. This is because the compounds contained in G. boninense are stronger than those in P. Polymyxa B32/77. while a comparative inhibition test showed that the P. Polymyxa B32/77 bacteria was able to inhibit the growth of R. solanacearum.